If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -58 = y + -16 Reorder the terms: -58 = -16 + y Solving -58 = -16 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. -58 + -1y = -16 + y + -1y Combine like terms: y + -1y = 0 -58 + -1y = -16 + 0 -58 + -1y = -16 Add '58' to each side of the equation. -58 + 58 + -1y = -16 + 58 Combine like terms: -58 + 58 = 0 0 + -1y = -16 + 58 -1y = -16 + 58 Combine like terms: -16 + 58 = 42 -1y = 42 Divide each side by '-1'. y = -42 Simplifying y = -42
| x+1(x+13)=85 | | 2(3x+4)-5=7-x | | 8x+7+12x=-5x-43 | | 5x-.20=.80 | | 6y^2=7y-2 | | x^3-49x-686=0 | | 10=.5mv^2 | | 8r+6+4r-1=14 | | 8-(2*x)=x+17 | | 20v^2-41vt+20t^2=0 | | 10=3(x-1)-(x-7) | | x+24-9x=-80 | | 4x=81/16 | | 36/x=12 | | S-1.4x=5.1 | | X^2+1.4x+.49=.81 | | 9a-6a+3a= | | -2(4y-4)-y=-2(y-4) | | 12x-17=6x+7 | | 4*15*6= | | 3(2c-3)-6=4c+9 | | 3u=30-2u | | X-(-10)=15 | | 3x+17=3(x+2)+11 | | x-3/10 | | 5x+3=2x-3+3x | | 7x+6=3x+8 | | 2x-5y=-45 | | -k-8(8k-6)=-16-k | | 1-4i= | | R-15=-12 | | 15500=C+0.30(15500) |